Manajemen Layanan Perpustakaan Dalam Meningkatkan Minat Baca Siswa di Perpustakaan SMA Negeri 3 Ponorogo - Aski Nur Azizah; Wilis Werdiningsih (Program Studi Manajemen Pendidikan Islam, Fakultas Tarbiyah dan Ilmu Keguruan, IAIN Ponorogo, 2023)
SMA Negeri 3 Ponorogo is a public school in Ponorogo Regency that has good library management. This can be seen from the library service programs that are well implemented. These programs include service-based programs and habituation-based programs. Both programs are able to encourage the increase of students' interest in reading at SMA Negeri 3 Ponorogo. This study aims to (1) find out the planning of library services in increasing student interest in reading at SMA Negeri 3 Ponorogo, (2) find out the implementation of library services in increasing student interest in reading at SMA Negeri 3 Ponorogo, (3) find out the evaluation of library services in increasing student interest in reading at SMA Negeri 3 Ponorogo. The research used a qualitative approach with a case study research type. The data analysis technique used is the Miles, Huberman, and Saldana model which includes data collection, data condensation, data presentation and decision making. The results of the study explain that (1) Planning library services in increasing student interest in reading in the library of SMA Negeri 3 Ponorogo is by planning service-based and habituation-based programs supported by collection procurement, infrastructure, and budget, (2) Implementation of library services in increasing student interest in reading in the library of SMA Negeri 3 Ponorogo is by implementing a) service-based programs implemented in circulation services with open types of services this aims to bind student attractiveness, b) habituation-based programs are implemented with the School Literacy Movement 15 Minutes before the subject starts, (3) Evaluation of library services in increasing student interest in reading at the SMA Negeri 3 Ponorogo library, namely by conducting meetings, monitoring, and follow-up in order to improve library services in increasing student interest in reading at the SMA Negeri 3 Ponorogo library.